Kewirausahaan Berbasis E-Commerce Untuk Meningkatkan Pendapatan Keluarga di Polsek Porsea - Guntur Maha Putra; Ahmad Muhazir; Jeperson Hutahaean; Arridha Zikra Syah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Porsea is one of the sub-districts in Toba Samosir. Toba Samosir Regency is geographically located between 2º24 '-2º37' LU and 99º03 '-99º16' BT. The agricultural sector is a top priority in the pillars of development in Toba Samosir Regency, because it has a large enough role and almost 90 percent of the people in the area work as farmers. Seeing the potential of the region and business opportunities, it is necessary to have facilities and strategies to distribute local products in the form of agriculture and other sectors with e-commerce-based marketing technology to reach a wider market / market. Community service activities on the topic of e-commerce-based entrepreneurship are carried out at the Porsea Police Office aimed at providing knowledge and skills about e-commerce, so that the knowledge gained can be implemented and is expected to increase family income from the potential of existing regions, so that it can eventually be transmitted to the surrounding communities as one of the work programs of the Porsea Sector Police to improve the living standards of the surrounding community